THE PORTRAIT OF EFL TEACHER IN ONLINE LEARNING DURING PANDEMIC COVID-19: A CASE STUDY IN STATE SENIOR HIGH SCHOOL NUMBER 8 JAMBI - Risa Anggraini (Journal MELT (Medium for English Language Teaching), 2021)
Pandemic Covid-19 is still on going in all over the world right now. This influences many things, education system, one of examples. Therefore, teachers should deal with the distance learning because of the pandemic. So that this research addresses to explore the portrait of EFL teacher in online learning during pandemic Covid-19. The particant in this research is an English teacher and and the site of the research is in State Senior High School Number 8 Jambi. The researcher uses case study qualitative research method design. Researcher collects the data through in-depth interview and uses interview protocol to guide the interview. The form of the questions is semi-structured interview which meant that researcher can prolong the interview question during its process of doing the interview with the participant. Findings of the research are explained through some primary themes, they are 1) Teacher’s burnout in online learning, 2) Teachers’ challenges and difficulties in online learning, and 3) Teachers’ solutions to overcome the problems appeared in online learning.  Also, there are both positive and negative portrait of online learning in terms of the systems, students’ motivations, and students’ learning objectives.